A prospective randomized study comparing 25-G and 22-G needles of a new platform for endoscopic ultrasound-guided fine needle aspiration of solid masses. Issue 1 (January 2016) - Carrara, Silvia; Anderloni, Andrea; Jovani, Manol; Di Tommaso, Luca; Rahal, Daoud; Hassan, Cesare; Ridola, Lorenzo; Federico, Davide; Loriga, Alessandra; Repici, Alessandro
Abstract: Background: A new needle platform for endoscopic ultrasound-guided fine-needle aspiration biopsy has been developed that allows interchangeability of all needle sizes. Aims: To prospectively compare the efficacy of the new 25-G needles and 22-G needles for obtaining an adequate aspirate of solid masses. Methods: Randomized controlled trial of 144 patients referred for endoscopic ultrasound-guided fine-needle aspiration of solid pancreatic masses, intraparietal tumours, or lymph-nodes, randomized to the 25-G or 22-G needle arms. Results: An adequate specimen was obtained from 74.3% of cases. The sample tended to be more adequate in the 25-G compared to the 22-G group (81% vs. 68%; p  = 0.09). Crossover was required in 14 (19%) and 12 (17%) cases in the 22-G and in the 25-G groups, respectively ( p  = 0.7). The overall rate of adequacy improved from 74% before crossover to 90% after crossover ( p  < 0.01). When comparing the two groups after crossover, the rate of obtaining adequate samples was significantly higher in the 25-G arm than in the 22-G arm (95.8% vs. 86.1%; p  = 0.03). Conclusions: The 25-G needle was superior to the 22-G needle for endoscopic ultrasound-guided fine-needle aspiration biopsy. The adequacy and diagnostic accuracy improved after crossover, reaching 90%.